2015
DOI: 10.4028/www.scientific.net/amm.773-774.69
|View full text |Cite
|
Sign up to set email alerts
|

Novel Straight Type Aortic Cannula with Spiral Flow Inducing Design

Abstract: Aortic cannula is one of major factors leading to adverse events such as thrombosis and atherosclerosis development during open heart surgery, due to oxygenated blood outflow with high velocity jet from heart lung machine (HLM) when exiting the cannula tip into the ascending aorta. It was discovered, and validated by several researchers that blood flow out of the left ventricle into the aorta is spiral in nature. In this study, a novel design in which internal profile of the cannula was made to induce spiral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…producing low wall shear stress) and assessing the aorta's three aortic branch artery flow integrity. [7][8][9] However, clinical studies have shown measurable emboli throughout cardiac CPB surgery, and so it would be more prudent to examine emboli pathlines and their patterns. 10,11 Yet, only a few studies have scrutinised the AC's influence on arterial emboli transport, leaving a gap of knowledge on how varying AC parameters during surgery contributes to the pathophysiology of neurologic deficits.…”
Section: Introductionmentioning
confidence: 99%
“…producing low wall shear stress) and assessing the aorta's three aortic branch artery flow integrity. [7][8][9] However, clinical studies have shown measurable emboli throughout cardiac CPB surgery, and so it would be more prudent to examine emboli pathlines and their patterns. 10,11 Yet, only a few studies have scrutinised the AC's influence on arterial emboli transport, leaving a gap of knowledge on how varying AC parameters during surgery contributes to the pathophysiology of neurologic deficits.…”
Section: Introductionmentioning
confidence: 99%